Investigation of Biophysical Migration Parameters for Normal Tissue and Metastatic Cancer Cells After Radiotherapy Treatment - Panzetta, Valeria; La Verde, Giuseppe; Pugliese, Mariagabriella; Arrichiello, Cecilia; Muto, Paolo; La Commara, Marco; D'Avino, Vittoria; Netti, Paolo A.; Fusco, Sabato (Frontiers in Physics, 2020)
A large body of literature has demonstrated that the mechanical properties of microenvironment have a key role in regulating cancer cell adhesion, motility and invasion. In this work, we have introduced two additional parameters, named cell trajectory extension and area travelled by cell, to describe the tendency of healthy and tumor cells to move in a directional way when they interact with physio-pathological substrates, characterized by stiffnesses of 1-13 kPa, before and after treatment with 2 doses of X-rays (2 and 10 Gy). We interpreted these data by evaluating also the impact of substrate stiffness on 2 morphological parameters which indicate not only the state of cell adhesion, but also cell polarization, prerequisite to directional movement, and the formation of protrusions over cell perimeters. We believe that a so wide analysis can give a comprehensive and easily readable overview of effects of radiation therapy on cell-ECM crosstalk when used as therapeutic agent.